Rethinking Islamic studies : from orientalism to cosmopolitanism - Martin, Richard C.; Ernst, Carl W., 1950- (UPCC book collections on Project MUSE., 2010)
A groundbreaking response to the challenges of interpreting Islamic religion in the post-9/11 and post-Orientalist era.